Analysis of salivary flow rate, biochemical composition, and redox status in orchiectomized spontaneously hypertensive rats - de Oliveira, Ana Carolina Fujimori [UNESP]; Brito, Victor Gustavo Balera [UNESP]; Ramos, Guilherme Henrique Alves dos Santos [UNESP]; Werlang, Matheus Lima Cypriano [UNESP]; Fiais, Gabriela Alice [UNESP]; Dornelles, Rita Cássia Menegati [UNESP]; Antoniali, Cristina [UNESP]; Nakamune, Ana Cláudia de Melo Stevanato [UNESP]; Fakhouri, Walid D.; Chaves-Neto, Antonio Hernandes [UNESP] (Elsevier, 2023)
Objective: This study aimed to analyze the salivary flow rate, biochemical composition, and redox status in orchiectomized spontaneously hypertensive rats (SHR) compared to normotensive Wistar rats. Design: Thirty-two young adult male SHR and Wistar (3-months-old) rats were randomly distributed into four groups; either castrated bilaterally (ORX) or underwent fictitious surgery (SHAM) as Wistar-SHAM, Wistar-ORX, SHR-SHAM, and SHR-ORX. Two months beyond castration, pilocarpine-induced salivary secretion was collected from 5-month-old rats to analyze salivary flow rate, pH, buffer capacity, total protein, amylase, calcium, phosphate, sodium, potassium, chloride, thiobarbituric acid reactive substances (TBARs), carbonyl protein, nitrite, and total antioxidant capacity. Results: The salivary flow rate was higher in the Wistar-ORX compared to the Wistar-SHAM group, while remaining similar between the SHR-SHAM and SHR-ORX groups. ORX did not affect pH and salivary buffer capacity in both strains. However, salivary total protein and amylase were significantly reduced in the Wistar-ORX and SHR-ORX compared to the respective SHAM groups. In both ORX groups, salivary total antioxidant capacity and carbonylated protein were increased, while lipid oxidative damage (TBARs) and nitrite concentration were higher only in the Wistar-ORX than in the Wistar-SHAM group. In the Wistar-ORX and SHR-ORX, the salivary calcium, phosphate, and chloride were increased while no change was detected in the SHAM groups. Only salivary buffering capacity, calcium, and chloride in the SHR-ORX adjusted to values similar to Wistar-SHAM group. Conclusion: Hypertensive phenotype mitigated the orchiectomy-induced salivary dysfunction, since the disturbances were restricted to alterations in the salivary biochemical composition and redox state.
Keywords: Electrolytes; Hypertension; Orchiectomy; Oxidative Stress; Saliva; Salivary Proteins and Peptides